Evulation of strip rust resistance gene and transfer of Yr15 into Indian wheats (Triticuln speices) - VINOD, VINOD; SIVASAMY, M; PRASHAR, M; MENON, M K; SINHA, V C; TOMAR, S M S (The Indian Journal of Agricultural Sciences, 2011)
A study was conducted during 1999-2004 at the IARI Regional Station, Wellington; and Indian Agricultural Research Institute, New Delhi, to critically evaluate 47 stocks, mostly ofwinter growth habit of hexaploid wheat (Triticum aestivum L. emend. Fiori & Paol.), carrying diverse specific genes, 10 near-isogenic lines in Avocet background, 12 accessions of T. spalla L., 35 exotics of wild emmer (T. dicoccoides Koem. ex Schweinf) and a few Indian wheat cultivars for adult plant resistance to stripe rust at Wellington and Lahaul Spiti for 8 seasons. All the genes except Yrl, Yr2, Yr6, Yr7, Yr18, Yr20, Yr21, Yr22, Yr23 and Yr27 conferred high to moderate degree of resistance to stripe rust races prevailing in southern and northern hills. Sixty per cent of T. dicoccoides accessions and most ofthe T. spelta strains exhibited adult plant resistant to stripe rust. The gene Yr15 originating from T. dicoccoides '025' was incorporated through judicious backcrossing into popular wheat cultivar 'HD 2329' and in an advance line 'BM 287'. The study on mode of inheritance and test of allelism showed that HD 2329*5/ 'V 763..2312' indeed carries resistance imparted by Yr15, which is of dominant nature. The availability of Yr15 in the background ofadapted wheat will enhance its use in wheat breeding in India and elsewhere.